The Effect of Metacognition Awareness on the Critical Thinking Skills of Elementary School Prospective Teachers - Chumdari Chumdari; Idam Ragil Widianto Atmojo; Roy Ardiansyah; Aisyah Shintawati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The ability to engage in critical thinking is crucial for students to effectively navigate the challenges of contemporary society. Metacognition awareness is a key indicator of an individual's critical thinking abilities. Metacognitive awareness can enhance one's cognitive control by incorporating critical thinking to regulate the thinking process. This study aimed to examine the impact of metacognitive awareness on the critical thinking abilities of PGSD (Primary School Teacher Education) students at Universitas Sebelas Maret during the 2022/2023 academic year. This study employed a quantitative methodology known as associative research. The study's population consisted of second-semester students who were selected using cluster random selection as the sampling technique. The study employed data analysis approaches that encompassed descriptive statistical analysis as well as inferential statistics, which involved doing preliminary analysis tests and hypothesis testing. The study's findings were determined by a significance test of the regression coefficient (T-test). The results indicated that the calculated t-value (2.049) was greater than the critical t-value (1.982), and the significance level (Sig.) of 0.042 was less than the threshold of 0.05. The multiple linear regression coefficient exhibited a positive value of 0.384, signifying a unidirectional link. The heightened awareness of metacognition led to a subsequent improvement in critical thinking abilities, with a determination coefficient of 20%. The findings demonstrated that the metacognitive awareness had an impact on the critical thinking abilities of PGSD students at Universitas Sebelas Maret during the 2022/2023 academic year.